TINJAUAN KONSEP DIRI DAN DIMENSINYA PADA ANAK DALAM MASA KANAK-KANAK AKHIR - Beatriks Novianti Kiling; Indra Yohanes Kiling (Program Studi bimbingan Konseling PPs UNM Makassar, 2015)
Individual self-concept is manifested in things that is related to that individual. Views about one’s self, self-evaluation, and expectation to one’s self formed the individual self-concept. Awareness of self-concept from the view of psychology would help a good and positive self-concept. This positive self-concept would in turn develop positive behaviours and interactions in daily life. This article discuss the concept of self-concept from psychological literatures and perspective. Dimensions, aspects, and factors of self-concept would be discussed and related to children’s situation in late childhood stage. Parents, teachers, and also the surrounding environment have important role in shaping self-concept of children. Social support and positive behavior model from the children’s closest persons and also the community will help in creating positive self-concept that in turn will support the transition to teenager phase. This article hopefully will be able to stimulate researcher to conduct further relevant research concerning children’s self-concept.